ASSESSING THE NEED AND CONSEQUENCES OF TERRITORIAL TRANSFORMATION OF RURAL SETTLEMENTS FROM THE PERSPECTIVE OF PROVIDING MUNICIPAL SERVICES - A. G. Ataeva; G. V. Zinnurova (Вестник университета)
The issues of transformation of municipal formations from the standpoint of quality and accessibility of municipal services have been considered. The study on the example of the unification of rural settlements of the Republic of Bashkortostan has been carried out. It has been analysed whether the unification of municipal formations will affect the provision of social services by municipal institutions. It has been established that the enlargement of rural settlements will slightly affect the accessibility of municipal services provided by municipal institutions. The need and consequences of the unification of municipal formations from the point of view of the financial capabilities of local governments to tackle issues of local importance also have been assessed. It has been determined that the unification of rural settlements can to some extent solve the problem of reducing administrative costs and increasing the financing of other issues of local importance. However, the solution of the problems of accessibility and quality of municipal services should be implemented not only by administrative methods through the enlargement of municipalities, but also using the tools of inter-municipal cooperation.